Optimizing Microclimate Comfort in Macao: ENVI-Met Simulation of High-Density Urban Layouts Under the Climate in the Lingnan Area - Xun Zhou; Yichen Sun; Tianyu Li; Yaming Zhou; Tao Tan; Chengzhi Yu; Siyang Dai (Atmosphere)
In the context of increasing urbanization, understanding the influence of urban spatial layouts on microclimatic conditions has become crucial, particularly in high-density reclaimed areas like those in the Macao Peninsula, where optimizing thermal comfort is essential for enhancing residents’ quality of life and promoting sustainable urban development. For this study, we assessed high-density reclaimed plots on the Macao Peninsula for a detailed case study. We conducted on-site measurements along with simulations using ENVI-met software, comparing datasets to ensure model accuracy and reliability. Through careful adjustment of simulation parameters to accurately reflect real-world conditions, we found that building layout and size have a significant effect on the Physiologically Equivalent Temperature (PET). Notably, in the unique climate of the Lingnan area, courtyard layouts demonstrably block external heat and wind, fostering a significantly more comfortable internal microclimate. This design strategy provides not only generous public space for fostering community activities and stronger social bonds, but also creates a visually appealing and cohesive aesthetic. This research seeks to improve resident comfort, optimize urban energy efficiency, and promote sustainable urban development principles. Accordingly, our findings serve as a valuable adaptation reference for urban environmental planning initiatives under the climate in the Lingnan area.